AN ANALYSIS OF FACTORS INFLUENCING TOURISTS’ VISIT DECISION - Fajrin, Nurul Komara; Oebit, Cut Edwina Safia (Teropong : Jurnal Manajemen dan Bisnis, 2023)
This study examines the factors influencing tourists' decision to visit "Kalibiru Tourist Village" in Yogyakarta Province, Indonesia. The declining number of visitors to this area prompted the investigation. The study focuses on three independent variables: Travel Motivation, Electronic Word-of-Mouth (E-WoM), and Destination Image. Two hundred and five respondents who had previously visited the area participated in the study. The data was analyzed using Structural Equation Modeling (SEM) with the LISREL statistical application. The findings indicate that all the variables significantly impact tourists' decision to visit the area.